2015
DOI: 10.5603/cj.a2015.0032
|View full text |Cite
|
Sign up to set email alerts
|

Survival after alcohol septal ablation versus conservative therapy in obstructive hypertrophic cardiomyopathy

Abstract: 08-0.60; p = 0.003) and maximal septal thickness (HR 1.14; p = 0.011). Conclusions:In patients with severe drug-refractory obstructive HCM, survival after ASA is favorable and better than that of conservative therapy. ASA seems to improve survival. (Cardiol J 2015; 22, 6: 657-664)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(57 reference statements)
1
3
1
1
Order By: Relevance
“…Similar to our data, a study conducted by Vriesendorp et al (24) reported a 10-year overall survival of 84.0% of MT group, but their study cohort were mildly symptomatic or asymptomatic (NYHA class I/II) patients with HOCM. Our survival rate of MT group was higher compared with two other studies with 10-year overall survival of 75.8% (Ball et (26). This might be due to the fact that these two studies involved some HOCM patients with NYHA class III/IV in the MT group, and multiple studies have demonstrated that for patients with HOCM, NYHA class III/IV is independently associated with worse prognosis (8,27).…”
Section: Discussioncontrasting
confidence: 55%
“…Similar to our data, a study conducted by Vriesendorp et al (24) reported a 10-year overall survival of 84.0% of MT group, but their study cohort were mildly symptomatic or asymptomatic (NYHA class I/II) patients with HOCM. Our survival rate of MT group was higher compared with two other studies with 10-year overall survival of 75.8% (Ball et (26). This might be due to the fact that these two studies involved some HOCM patients with NYHA class III/IV in the MT group, and multiple studies have demonstrated that for patients with HOCM, NYHA class III/IV is independently associated with worse prognosis (8,27).…”
Section: Discussioncontrasting
confidence: 55%
“…Second, Yang et al showed similar results as Ball on survival in the ASA patients (23). Both these studies compared prognostic indicators of these two treatment strategies and demonstrated a superiority of invasive access, respectively ASA, in patients with HOCM.…”
Section: Tab 2 Development Of Parameters In Both Groups (Comparisonsupporting
confidence: 61%
“…These anatomic abnormalities include abnormally long MV leaflets (anterior or posterior), bifid PM, and papillary muscle attachment directly to the mitral leaflet base. These anomalies can cause LVOTO even in the absence of septal hypertrophy [ 6 ]. Figure 4 .…”
Section: The Mitral Valvementioning
confidence: 99%
“…Importantly, there is a distinct advantage to invasive management over medical treatment of HOCM patients [ 6 ]. Indeed, more recently, other contributing factors in LVOTO were disclosed: the mitral valve (MV) and its subvalvular apparatus (SVA).…”
Section: Introductionmentioning
confidence: 99%